From Donor to the Lab: A Fascinating Journey of Primary Cell Lines - Richter, Magdalena; Piwocka, Oliwia; Musielak, Marika; Piotrowski, Igor; Suchorska, Wiktoria M.; Trzeciak, Tomasz (Frontiers in Cell and Developmental Biology, 2021)
Primary cancer cell lines are ex vivo cell cultures originating from resected tissues during biopsies and surgeries. Primary cell cultures are objects of intense research due to their high impact on molecular biology and oncology advancement. Initially, the patient-derived specimen must be subjected to dissociation and isolation. Techniques for tumour dissociation are usually reliant on the organisation of connecting tissue. The most common methods include enzymatic digestion (with collagenase, dispase, DNase), chemical treatment (with EDTA and EGTA), or mechanical disaggregation to obtain a uniform cell population. Cells isolated from the tissue specimen are cultured as a monolayer or three-dimensional culture, in the form of multicellular spheroids, scaffold-based cultures (i.e. organoids), or matrix-embedded cultures. Every primary cell line must be characterised to identify its origin, purity, and significant features. The process of characterisation should include different assays utilising specific (extra- and intracellular) markers. The most frequently used approaches comprise immunohistochemistry (IHC), immunocytochemistry (ICC), Western blot (WB), flow cytometry (FC), RT-qPCR, karyotyping, confocal microscopy, and next-generation sequencing (NGS). The growing body of evidence indicates the validity of the usage of primary cancer cell lines in the formulation of novel anti-cancer treatments and their contribution to drug development.